Pemanfaatan Hasil Akreditasi dan Kredibilitas Asesor Sekolah/Madrasah - Hendarman -- (Jurnal Pendidikan dan Kebudayaan, 2013)
This study concerned on the effectiveness of accreditation process with two objectives, namely (1) how accreditation results are utilized by the local government at provincial/district/city levels in determining policies and programs, and (2) how credibility of assesors could assure accountability and accuracy of accreditation results. The method used was meta-analysis using both primary and secondary data. The primary data was obtained through the interviews to Heads of School/Madrasah Accreditation Board at Provincial level (BAP-S/M). Whereas, the sources of secondary data were from School/Madrasah National Accreditation Board (BAN-S/M), Centre for Educational Data and Statistics (PDSP) the Ministry of Education and Culture, BAP-S/M websites, media and official regulations, as well as related studies. The study results showed that local government at provincial/district/city levels tend to not follow-up the accreditation results, and credibility of assesors is not being evaluated in such an accurate and accountable manner as the instrument used was not relevant.Â ABSTRAKÂ Penelitian ini untuk mengkaji efektivitas penyelenggaraan akreditasi pada sekolah/madrasah dengan dua tujuan, yaitu (1) bagaimana hasil akreditasi dimanfaatkan oleh pemerintah daerah pada tingkat provinsi/ kabupaten/ kota dalam penentuan kebijakan dan program, dan (2) bagaimana kredibilitas asesor dapat menjamin hasil akreditasi yang akurat dan akuntabel. Metode yang digunakan adalah meta-analysis dengan menggunakan data primer dan sekunder. Data primer diperoleh dari wawancara dengan ketua Badan Akreditasi Provinsi Sekolah/Madrasah (BAP-S/M). Data sekunder bersumber dari Badan Akreditasi Nasional Sekolah/Madrasah (BANS/M), Pusat Data Statistik Pendidikan (PDSP) Kementerian Pendidikan dan Kebudayaan, website BAP-S/M, media serta dokumen resmi peraturan perundang-undangan, dan hasil-hasil studi terkait. Hasil penelitian menunjukkan bahwa hasil akreditasi belum sepenuhnya ditindaklanjuti oleh pemerintah daerah di tingkat provinsi/kabupaten/kota, dan kredibilitas asesor sekolah/madrasah belum dinilai secara akurat dan akuntabel karena menggunakan instrumen yang kurang relevan.